Towards guidelines for tertiary distance education courseware design : a textlinguistic perspective - Steenekamp, Jan Harm (2012)
M.A. === The new democratic South Africa has opened up a number of unique opportunities and challenges for distance education at tertiary level. Tertiary institutions, however, also face several serious problems that must be addressed in order to rectify the educational imbalances in the country. Due to the policy of equal opportunities for all regardless of race, creed, colour and culture, tertiary education institutions are experiencing an unprecedented influx in student numbers. Residential universities and technikons can accommodate this influx only up to a certain point due to limited physical facilities such as residences and lecture rooms. For this and other reasons, distance education is rapidly becoming the primary means of education, not only in South Africa but also in many countries around the world. It offers an immediate and practical solution to the problem of high student numbers. Some of the advantages of distance education are: • greater numbers of students can be reached throughout the country • students in rural areas have the same opportunities for education as their urban counterparts • imbalances can be addressed more effectively on a wider scale, including the rural areas • courses are generally more affordable • because of their technical nature, courses are often more directly related to the requirements of industry than traditional courses • accommodation for students and physical lecturing facilities are not an issue. The disadvantages, however, are: 1 Chapter 1: Instructional Courseware Design: Introduction lack of direct contact with lecturers lack of student support systems, such as contact with other students and the availability o lecturers to help solve learning and other problems the fact that the primary means of communication and instruction is the written word with limited opportunities for direct verbal contact limited or inadequate administrative support To overcome these problems, the "distance" in distance education mu